Notes to Philosophy 167: Class 14 -- Newton's De Motu Corporum, Version 3 -- Part 13. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Conception of Evidence in De Motu Version 1 -- The Conception of Evidence in Version 3 -- Intimations of a New Conception of Evidence -- An Evolution in Conceptions of Evidence -- Parallel Evolution in the Science of Orbital Motion -- Three 17th Century Revolutions in Evidence.; Generally corresponds to the video segment: Class 14, Part 13.